The Influence of Taxation System Fairness, Financial Condition and Subjective Beliefs on Tax Compliance by Corporate Taxpayers with Intentions to Behave Obediently as Intervening Variables: Pengaruh Keadilan Sistem Perpajakan, Kondisi Keuangan dan Keyakinan Subjektif Terhadap Kepatuhan Perpajakan Oleh Wajib Pajak Badan dengan Niat Berperilaku Patuh Sebagai Variabel Intervening - Alam, Ornela Aprillia; Ernandi, Herman (Indonesian Journal of Innovation Studies, 2022)
This study aims to determine the effect of the fairness of the taxation system, financial condition and subjective beliefs on tax compliance by corporate taxpayers with the intention of obedient behavior as an intervening variable. The sampling technique used saturated sampling by distributing questionnaires, so that 38 respondents were obtained. The data analysis technique used is the Outer Model to test the validity and reliability. Next is the Inner Model to test the hypothesis by using the SmartPLS version 3.0 program tool. The results of this study indicate that the fairness of the taxation system has a significant effect on tax compliance by corporate taxpayers while for financial conditions, subjective beliefs and intentions to behave obediently do not have a significant effect, then the fairness of the taxation system, financial condition and subjective beliefs do not significantly affect tax compliance by corporate taxpayers with intention to behave obediently as an intervening variable.